2022
DOI: 10.21203/rs.3.rs-1252972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forest tree species distribution for Europe 2000-2020: mapping potential and realized distributions using spatiotemporal Machine Learning

Abstract: Paper describes a data-driven framework based on spatio-temporal ensemble machine learning to produce distribution maps for 16 forest tree species (Abies alba Mill., Castanea sativa Mill. , Corylus avellana L., Fagus sylvatica L., Olea europaea L., Picea abies L. H. Karst., Pinus halepensis Mill., Pinus nigra J. F. Arnold, Pinus pinea L., Pinus sylvestris L., Prunus avium L., Quercus cerris L., Quercus ilex L., Quercus robur L., Quercus suber L. and Salix caprea L.) at high spatial resolution (30 m). Tree occu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…All the analysis were performed using R (version 4.1.1) (R Core Team, 2021) and, specifically, the mlr package (Bischl et al, 2016). For more details on the hyperparameter space used for the other component models and the overall architecture of the ensemble model, see Bonannella et al (2022).…”
Section: Model Building and Evaluationmentioning
confidence: 99%
“…All the analysis were performed using R (version 4.1.1) (R Core Team, 2021) and, specifically, the mlr package (Bischl et al, 2016). For more details on the hyperparameter space used for the other component models and the overall architecture of the ensemble model, see Bonannella et al (2022).…”
Section: Model Building and Evaluationmentioning
confidence: 99%
“…This loss in precision may lead to similar limitations, especially in the case of infrared for vegetation-related modeling. However, Bonannella et al (2022) achieved high accuracy (0.81-0.89) using the Byte-scale Landsat data when classifying multiple different tree species, suggesting this may not be a significant limitation.…”
Section: The Cost Of Accessibility and Analysis-readinessmentioning
confidence: 96%
“…and realized distribution of 16 tree species (Bonannella et al, 2022), monthly airborne fine particulate matter levels (Ibrahim et al, 2022), 43 CORINE land cover classes (Witjes et al, 2022), and daily aerosol optical depth levels (Ibrahim et al, 2021). We aim to continuously extend the feature space of the data cube, both by producing new datasets and hosting harmonized products created by third parties.…”
Section: Future Workmentioning
confidence: 99%
“…We implemented the workflow in the Python (Van Rossum and Drake, 2009) and R (R Core Team, 2021) programming languages. More technical details on preprocessing steps and packages used according to ODMAP (Zurell et al, 2020) are presented in Table S1 (found in https://zenodo.org/record/6516728/preview/Supplementary_material.pdf# subsection.0.1) (Bonannella et al, 2022).…”
Section: General Workflowmentioning
confidence: 99%
“…Results of this operation are shown in Table S2 and Fig. S1 (found in https://zenodo.org/record/6516728/preview/Supplementary_ material.pdf#subsection.0.2) (Bonannella et al, 2022).…”
Section: Spatial Thinningmentioning
confidence: 99%